ARTIKEL PEMBINAAN MINAT BACA PADA PERPUSTAKAAN SEKOLAH: GAGASAN & KONSEP: MINAT BACA - Ali Hasan, Nurhayati (Indonesian Journal of Library and Information Science, 2020)
The primary function of the school library is to support school efforts to develop bacis literacy skills of students : skills for finding, accessing and using information from various sources for personal and academic reasons so that student will be information literate. Despite all the emphasis on “information literacy “ of school library, today’s school librarian especially in Indonesia still have a key role to play in the promotion of reading since students reading habit or interest is relatively slow. Some strategies are suggested to be applied by trained librarian and teacher librarian in promoting reading for students; provide the tools to help young people access books, not to be judgmental about children’s reading choices & school librarians should model positive reading behaviour, Demonstrate that reading is valued, Make reading social and Create opportunities for reluctant readers to share reading with an active or enthusiastic reader. Besides that, Literacy Development should be considered whether in stage to learn to read or read to learn